Prestise Batu Na Pir Sebagai Sarana Peningkatan Status Sosial Masyarakat Suku Batak Toba di Desa Silalahi II, Sumatera Utara - Limbong, Angli Rosalia; Zuryani, Nazrina; Aditya, I Gst. Ngr Agung Krisna (Lenggogeni Data Publishing, 2024)
This study examines the tradition of building